2010
DOI: 10.1016/j.jcrs.2009.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the early biomechanical effects of hyperopic and myopic laser in situ keratomileusis

Abstract: PURPOSE-To compare changes in corneal hysteresis (CH) and the corneal resistance factor (CRF) in myopic and hyperopic laser in situ keratomileusis (LASIK) and evaluate their relationship with the number of photoablative pulses delivered, a surrogate for ablation volume. SETTING-ClevelandClinic Cole Eye Institute, Cleveland, Ohio, USA. METHODS-Preoperative and 1-week postoperative OcularResponse Analyzer measurements in eyes that had femtosecond-assisted LASIK were studied retrospectively. Changes in CH and CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
2
12
0
7
Order By: Relevance
“…glaucoma, keratoconus and postrefractive eyes). A significant change in the biomechanical properties of the cornea is found after PRK, LASIK and epi-LASIK, measured with ORA [4][5][6]9,[16][17][18][19][20][21][22]. The decrease in the biomechanical values was significantly larger after LASIK than after PRK, three months postoperatively, with the same preoperative data [20].…”
Section: Discussionmentioning
confidence: 99%
“…glaucoma, keratoconus and postrefractive eyes). A significant change in the biomechanical properties of the cornea is found after PRK, LASIK and epi-LASIK, measured with ORA [4][5][6]9,[16][17][18][19][20][21][22]. The decrease in the biomechanical values was significantly larger after LASIK than after PRK, three months postoperatively, with the same preoperative data [20].…”
Section: Discussionmentioning
confidence: 99%
“…As DCT IOP measurements were slightly lower in eyes of type 1 diabetic patients, the type 1 cohort may have had slightly lower IOPs than their type 2 counterparts. Corneal biomechanical properties have been shown to alter following corneal refractive 31,42,43 and cataract 44,45 surgery procedures, and it has been suggested that there may be a role for ORA metrics to better predict refractive outcomes of these procedures. 19 Our data show that compared with eyes of nondiabetic subjects, eyes of diabetic patients have altered corneal biomechanics that may be related to blood glucose concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72][73][74] Some studies showed a reduction of CH and CRF after LASIK -from 10.4 ± 1.7 mmHg to 9.3 ± 1.9 mmHg and from 10.1 ± 1.9 mmHg to 8.1 ± 1.8 mmHg, respectively. 59,71 For these parameters, however, no further changes occurred during a 6-months follow-up period, in contrast to progression of keratoconus.…”
Section: Impact Of Prk and Lasik On Ora Measurementsmentioning
confidence: 99%